2013
DOI: 10.1371/journal.pone.0070115
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Higher Order Patterns in Proteins: Immunologic Kernels

Abstract: By applying analysis of the principal components of amino acid physical properties we predicted cathepsin cleavage sites, MHC binding affinity, and probability of B-cell epitope binding of peptides in tetanus toxin and in ten diverse additional proteins. Cross-correlation of these metrics, for peptides of all possible amino acid index positions, each evaluated in the context of a ±25 amino acid flanking region, indicated that there is a strongly repetitive pattern of short peptides of approximately thirty amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…yielding a decamer peptide. This is consistent with prior observations that indicate that a decamer may be more likely to be initially excised than a nonamer (23). This selection process yielded a ranking of peptides for further study, where four were selected for testing.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…yielding a decamer peptide. This is consistent with prior observations that indicate that a decamer may be more likely to be initially excised than a nonamer (23). This selection process yielded a ranking of peptides for further study, where four were selected for testing.…”
Section: Resultssupporting
confidence: 93%
“…The amino acid substitutions in the exposed positions included P4: I>L, P5: N>Q, P6: F>I, A, L or Y, P7: E>D, P8: K>R. The B. melitensis proteome and the proteomes of an array of other pathogenic and microbiome bacteria were then searched to determine the occurrence of each of the alternate TCEM pentamer motifs P4-P8. Where a near neighbor was identified in B. melitensis , the flanking amino acids were noted, and the predicted binding to murine MHC I alleles was determined in the context of the native Brucella protein using previously described methods (21), and the probability of cathepsin cleavage at the C terminus of that peptide determined (22, 23).…”
Section: Methodsmentioning
confidence: 99%
“…Adding more realism, there will be cooperative influences at different positions, leading to positional correlations in amino acid preferences and reducing the number of compatible peptides (69). But although the example is shown for 9-mers, longer peptides are processed, presented, and recognized, which will increase the number of compatible peptides (70).…”
Section: Rationalizing the Specificity/cross-reactivity Duality Of Tcrsmentioning
confidence: 99%
“…In silico models based on these assumptions suggest that nearly half of CSF BCR variable regions from MS patients harbor potential antigenic idiotopes (9). These models included prediction of HLA-DR affinities (25,26), likelihood of endosomal processing by cysteine cathepsins (27,28) and modeling of tolerance likelihood based on T cell exposed motifs (TCEM) (9,29). It has previously been suggested that frequently occurring TCEM in variable regions (i.e., germline framework motifs) could be tolerogenic, while rare motifs [i.e., complementarity determining region (CDR) 3 or motifs resulting from mutations] potentially could be stimulatory to T cells (10,29).…”
Section: Introductionmentioning
confidence: 99%
“…The prediction models used to predict cathepsin cleavage, HLA affinity and TCEM of IGHV have been validated in silico (25)(26)(27)29), and for cathepsin cleavage also in vitro using monoclonal antibodies (28). It has however not been verified whether this or any other in silico model actually predicts a repertoire of idiotopes that actually have a corresponding T cell repertoire.…”
Section: Introductionmentioning
confidence: 99%